2013
DOI: 10.1021/es403260b
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Benzo[a]pyrene-Induced Toxic Effects in Japanese Medaka (Oryzias latipes) by 2,2′,4,4′-Tetrabromodiphenyl Ether

Abstract: Because polycyclic aromatic hydrocarbons (PAHs) and polybrominated diphenylethers (PBDEs) are ubiquitous and coexist in the environment and in wildlife, there are potential interactions between them that could cause toxic effects. In this study, the modulating effects of 2,2',4,4'-tetrabromodiphenyl ether (BDE47) and benzo[a]pyrene (BaP)-induced reproductive and developmental toxic effects in Japanese medaka (Oryzias latipes) were investigated by exposing adult Japanese medaka to BaP alone, BDE47 alone, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Owing to their highly lipophilic nature, slow metabolism, and high toxicity (Miniero et al, ; Sorg et al, ), they have a long half life in the body and cause many diseases such as hypertension, diabetes, metabolic syndrome, and atherosclerosis. Because humans are ubiquitously and simultaneously exposed to mixtures of these persistent organic pollutants (POPs) (Zhao et al, ), it is important to assess the mixture effects of multiple pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their highly lipophilic nature, slow metabolism, and high toxicity (Miniero et al, ; Sorg et al, ), they have a long half life in the body and cause many diseases such as hypertension, diabetes, metabolic syndrome, and atherosclerosis. Because humans are ubiquitously and simultaneously exposed to mixtures of these persistent organic pollutants (POPs) (Zhao et al, ), it is important to assess the mixture effects of multiple pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ERs, AR and THRs, involved in development and maintenance of the endocrine system, have been demonstrated to be targets of alkylphenols, phthalates (PAEs), dichlorodiphenyltrichloroethane and some metabolites of polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDE) 11 12 13 . Besides endocrine receptors, PXR and CAR, NRs that participate in metabolism of both endobiotics and xenobiotics to detoxify or bioactivate chemicals, can be activated by a variety of pharmaceuticals such as rifampicin, pesticides such as chlorpyrifos and methoxychlor, and other synthetic chemicals used in industry, such as PBDEs and BPA 14 15 16 17 In addition to these well-known NRs, there are more NRs, that, during the past decade, have been identified in genomes of several vertebrates. These include 48 NR genes in human ( Homo sapiens ), 47 genes in rat ( Rattus norvegicus ), 49 genes in mouse ( Mus musculus ) and 68 genes in the teleost puffer fish Fugu rubripes 18 19 .…”
mentioning
confidence: 99%
“…Although the microscopic examination of H&E‐stained slides suggests that the binary‐exposure category appears counter‐intuitively to exhibit a reduced level of liver injury compared with the single exposure categories, this would need to be confirmed in parallel standard toxicity assays looking at transcriptomic/protein alterations (e.g., CYP isoforms), enzyme leakage, energy status and genomic damage. To speculate on underlying mechanism, it has been found that the presence of BDE‐47 significantly reduces the toxic effects of B[ a ]P in Oryzias latipes larvae (Zhao et al, 2013). To this end, it has been noted that exposure to B[ a ]P can induce up‐regulation of CYP1A gene expression (Zhang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…CYP1A can metabolize organic pollutants into active intermediates, thus producing toxic effects. However, BDE‐47 exposure may significantly inhibit the expression of CYP1A , thus reducing the toxic effects of B[ a ]P (Zhao et al, 2013). The attenuation of B[ a ]P‐induced CYP1A expression by BDE‐47 was also observed in a previous in vitro test, in which L02 cells pre‐treated with BDE‐47 could significantly decrease B[ a ]P‐induced CYP1A expression (An et al, 2011).…”
Section: Discussionmentioning
confidence: 99%